Design and Development of Pulsatile Cardiovascular Flow Simulator and Comparative Assessment of Flow through Stenosed Blood Vessel - Bit, A.; Chattopadhyay, H.; Deshmukh, K.; Mukherjee, R.; Benim, A. C. (Pleiades Publishing Ltd, 2025)
The design, development, and validation of a physiological pulsatile cardiovascular flow simulator to analyse the hemodynamic behaviour in stenosed blood vessels is studied. The simulator consists of an innovative arrangement of peristaltic pumps to reproduce realistic arterial pulse waveforms, incorporating the higher harmonic components of physiological flow. Experimental investigations were performed using a laser Doppler velocimetry (LDV) system to evaluate the axial velocity, the wall shear stress (WSS), the turbulence intensity, and related flow parameters in vessels with varying stenosis severities (12.5, 25, and 50%). The observed results indicated that stenosis severity critically influences the flow structure, with higher blockages inducing significant velocity skewness, increased oscillatory WSS, and sustained post-stenotic disturbances. Flow reversal, vortex formation, and prolonged laminar recovery were observed downstream of severe stenoses. Comparative analyses with theoretical models validated the experimental accuracy, particularly in central and mid-radial zones. The study also introduced a method for determining the oscillatory shear index (OSI) and the relative residence time (RRT), identifying regions susceptible to atherogenesis. The simulator provides a reliable platform for replicating in vivo-like flow patterns in vitro, providing the valuable insights into the disease progression mechanisms and enabling future development of diagnostic and interventional strategies in cardiovascular medicine.
Keywords: pulsatile flow simulator; stenosed blood vessel; wall shear stress (WSS); oscillatory shear index (OSI); relative residence time (RRT); flow separation